Management of The Failed Latarjet Procedure: Outcomes of Revision Surgery With Fresh Distal Tibial Allograft. Issue 7 (29th July 2019) - Bernhardson, Andrew S.; Peebles, Liam A.; Murphy, Colin P.; Sanchez, Anthony; LaPrade, Robert F.; Provencher, Matthew T.
Objectives: A patient with recurrent instability after a failed Latarjet procedure remains a challenge to address. The vast majority of these result in large amounts of bone loss, resorption, and issues with retained hardware, and there is minimal literature that assesses outcomes of revision surgery following a failed Latarjet. The objective of this study was to determine the outcomes of patients who underwent revision surgery for a recurrent shoulder instability after a failed Latarjet procedure. Methods: All consecutive patients who presented with recurrent anterior shoulder instability after a Latarjet procedure were prospectively enrolled. Patients were included if they had a prior Latarjet, and a history and physical examination findings consistent with recurrent anterior shoulder instability. Patients were excluded if they had prior neurologic injury, a seizure disorder, bone graft requirements to the humeral head, or findings of multidirectional or posterior instability. History of shoulder instability was documented, including initial dislocation history, time of instability, number of prior procedures, and examination findings, as well as plain radiographic data and computed tomography (CT) scan obtained on all patients, and arthritis graded with Samilson and Prieto (SP) grade. All patients were treated with hardware removal, capsulo-labral release with subsequent repair and bony reconstruction via fresh distal tibial allograft to the glenoid. Outcomes pre- and post-revision were assessed with ASES (American Shoulder and Elbow Score), Single Assessment Numerical Evaluation (SANE), and Western Ontario Shoulder Index (WOSI), and statistically compared. All patients underwent a CT scan of the distal tibial allograft at a minimum time point 4 months after surgery. Results: There were 31 patients enrolled (all males), with mean age 25.5 (range, 19 to 38), and with a mean follow-up of 47 months (range, 36 to 60) after the revision with distal tibial allograft. All patients after their Latarjet presented with recurrent shoulder dislocation (11/31) or recurrent subluxation (20/31) and all patients had recurrent shoulder instability on examination. Radiographs demonstrated two fixation screws in all cases, mean SP grade of 0.5 (range, I to III), and CT scan demonstrated that mean 78% of the Latarjet coracoid graft had resorbed (range, 50% to 100%). Preoperative outcomes improved for ASES (40 to 92, p=0.001), SANE (44 to 91, p=0.001), and WOSI (1300 to 310, p=0.001). There were no recurrences, and a final CT scan of the distal tibia revision demonstrated a mean 92% of DTA remained, but 98% union at the glenoid-DTA interface. Conclusion: Although the failed Latarjet with subsequent instability remains a challenge, treatment with fresh a distal tibial allograft provided substantial improvement in terms of stability and function. The vast majority of the failed Latarjet procedures had near complete resorption of the coracoid graft and many had hardware complications. Additional long-term studies are necessary to determine the efficacy of this challenging revision population.